(untitled) (Revista Puertorriqueña de Psicologia, 2016)
Loss and death accompany us in every stage of our lives. Although they are normal and common experiences, they usually leave us confused, disturbed, and whith feelings and emotions that are difficult for us to understand. This paper present differents aspects and concepts related to loss, death, mourning, and bereavement. It describes and discuss the principal models concerning to death, mourning and the "grief-work" hypothesis, and the main theorists view about "normal" and "pathological" bereavement. Social aspects related to death and mourning are also discussed. Finally, some guides to clinical treatment for the bereaved patient are outlined.